2003
DOI: 10.1097/00005537-200310000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral suppression of distortion‐product otoacoustic emissions declines with age: A comparison of findings in CBA mice with human listeners

Abstract: Functional decline of the medial olivocochlear efferent system with age precedes outer hair cell degeneration. Loss of medial olivocochlear suppressive function may play a role in the development of presbycusis in both clinical cases and animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
54
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 54 publications
12
54
1
3
Order By: Relevance
“…Furthermore, it was shown that CBA mice, the widely accepted model of late-onset ARHL, showed better contralateral suppression of DPOAEs in young adults compared with the C57 early-onset ARHL strain. In terms of MOC efficacy in different parts of the cochlea, a stronger MOC effect in the low-and mid-frequency areas compared with the high-frequency area has been shown in other studies (Jacobson et al, 2003;Kim and Frisina, 2002). In this study, we could find that the morphological and functional phenotypes of C57 mice indicate that as compared to the CBA mice, C57 mice show greater dysfunction of the MOC efferent system as evidenced by abnormal morphology of the efferent OHC synapse.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, it was shown that CBA mice, the widely accepted model of late-onset ARHL, showed better contralateral suppression of DPOAEs in young adults compared with the C57 early-onset ARHL strain. In terms of MOC efficacy in different parts of the cochlea, a stronger MOC effect in the low-and mid-frequency areas compared with the high-frequency area has been shown in other studies (Jacobson et al, 2003;Kim and Frisina, 2002). In this study, we could find that the morphological and functional phenotypes of C57 mice indicate that as compared to the CBA mice, C57 mice show greater dysfunction of the MOC efferent system as evidenced by abnormal morphology of the efferent OHC synapse.…”
Section: Discussionsupporting
confidence: 68%
“…This suggests that deafferentation following noise damage predominantly affects high-threshold AN fibers, while sufficient numbers of low-threshold AN fibers remain responsive to sound. Normal hearing thresholds can also be accompanied by impaired function of efferent fibers that project from the brainstem to the cochlea (Kim et al, 2002;Jacobson et al, 2003;Zettel et al, 2007;Zhu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of this pathway ultimately leads to inhibition of the outer hair cell activity, and inhibition of DPOAE signals. A note on terminology: the modulation of DPOAE by the MOCS is commonly referred to as 'suppression' when it results in a reduction in DPOAE level [Abdala, 2001;James et al, 2002;Jacobson et al, 2003;James et al, 2005;James, 2011]. Considering that the MOCS can both suppress and enhance DPOAE, the effects are sometimes referred to as 'modulations' [Harrison et al, 2008].…”
mentioning
confidence: 99%